The Rise of Resilience in Education in Emergencies. Issue 3 (26th May 2020) - Shah, Ritesh; Paulson, Julia; Couch, Daniel
ABSTRACT: This article explores how resilience as a concept is being increasingly mobilised within the Education in Emergencies (EiE) community. Using content and a close textual analysis, it identifies the concept's growth in prominence within key EiE documents arguing it has been employed to serve a range of different purposes. It contends, however, that dominant conceptualisations of resilience within the EiE community are reflective of a number of shifts around the problem, subjects and purposes of education provision in such conflict-affected contexts. This serves to limit the transformative potential of resilience, particularly in regards to contributing to positive peace.